Three kinds of Muslim managers: lessons from the Qur'an - Fontaine, Rodrigue Ancelot Harvey (World Academy of Islamic Management (WAIM), 2019)
This study concerns Islamic management. Scholars agree that Surah al-Fatihah provides a summary of the entire Qur’an. In particular, Surah al-Fatihah identifies three kinds of people: people who have knowledge and apply it, people who have knowledge but do not apply it, and people who have no knowledge. However, other surahs provide further insights. Surah al-Asr, in particular, emphasizes the importance of enjoining “haqq” and enjoining “sabr”. These concepts are difficult to translate into English so a separate discussion is necessary to clearly identify these concepts. These concepts enable the author to conclude that the Qur’an provides a typology that divides Muslim managers into three separate categories.